Nutrition risk and validation of an HIV disease-specific nutrition screening tool in Ghana - Lauri Wright; Maxwell Bisala Konlan; Laurene Boateng; James B Epps (The South African Journal of Clinical Nutrition, 2021)
Objectives: The objectives of this study were to assess the nutritional status and the most commonly reported nutrition-related factors contributing to nutritional risk in people living with HIV/AIDS (PLWHA) in Ghana and the specificity and sensitivity of the Rapid Nutrition Screening for HIV disease tool (RNS-H) in this population. Design: A cross-sectional design was utilised. Patients were screened for nutritional status during a one-week period by clinic nurses using the RNS-H. Results were compared with a comprehensive nutritional assessment by a dietitian. Setting: The research was conducted in a public health clinic at the University of Ghana Hospital, Legon. Subjects Patients receiving care at the clinic were asked to participate. Outcome measures: The nutritional screening and nutritional assessment both resulted in participants being assigned to one of three nutritional statuses: ‘low risk’, ‘at risk’ and ‘high risk’. The association between the nutritional screening and nutritional assessment was measured. Results: The results of the nutritional status assigned by the RNS-H and nutritional assessment were compared. A total of 51 patients participated. A high prevalence of nutritional risk based on the RNS-S (54.9%) was found with 33.3% of the sample being malnourished. The most common nutrition-related complications were food insecurity, poor appetite, weight loss and diarrhoea. Conclusions: The RNS-H was found to have a strong specificity and sensitivity in a sample of Ghanaian PLWHA. Because of the nutritional risk and complexity of HIV in Ghana, nutritional screening using the RNS-H and nutrition care by a dietitian should be a standard of care.